Transformasi Hadis Nabi dari Klalsik, Modern dan Kontemporer - Latiful Wahid (Journal Khafi : Journal Of Islamic Studies, 2023)
The study of the transformation of the Prophet's traditions from the classical, modern to contemporary periods is an important research area in the science of hadith. This study aims to investigate changes and developments in the understanding and application of the Prophet's traditions from time to time. In this context, classic refers to the early period of Islam, modern refers to the following centuries, and contemporary includes the present. The research method used is a comprehensive analysis of a collection of hadith literature from various periods. The data collected includes hadith texts, works of well-known hadith scholars, and academic works that discuss the transformation of hadith. The results of the study show that there have been significant changes in the understanding and use of the Prophet's traditions from time to time